2018
DOI: 10.1002/jssc.201800507
|View full text |Cite
|
Sign up to set email alerts
|

Determination of selected emerging contaminants in freshwater invertebrates using a universal extraction technique and liquid chromatography accurate mass spectrometry

Abstract: A simple sample preparation method based on a modified liquid-phase extraction approach to extract selected pharmaceuticals and personal care products from freshwater organisms is described. Extracted samples were analysed using liquid chromatography with Q-Exactive plus hybrid quadrupole Orbitrap mass spectrometry, using 2.6 μm C18 media. A 0.1% v/v acetic acid/acetonitrile mobile phase was applied over a 20 min gradient. Method detection limits in full scan mode were ca. 0.04-2.38 ng of analyte per g of samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 35 publications
(52 reference statements)
1
6
0
Order By: Relevance
“…The sensitivity of the method was comparable to others that have determined pharmaceuticals and pesticides in invertebrates. For example, Inostroza et al, had method quantification limits (MQLs) of 0.01–2.13 ng g −1 wet weight (Inostroza et al, 2016), Althakafy et al, reported detection limits ranging 0.04–2.38 ng g −1 wet weight (Althakafy et al, 2018) and Munz et al, achieved LOQs of 0.1 to 9 ng g −1 wet weight (Munz et al, 2018). Linearity was acceptable (R 2 > 0.98) and the chromatographic separation showed good reproducibility with an average standard deviation in retention time of ±0.015 min ( n = 5).…”
Section: Resultsmentioning
confidence: 99%
“…The sensitivity of the method was comparable to others that have determined pharmaceuticals and pesticides in invertebrates. For example, Inostroza et al, had method quantification limits (MQLs) of 0.01–2.13 ng g −1 wet weight (Inostroza et al, 2016), Althakafy et al, reported detection limits ranging 0.04–2.38 ng g −1 wet weight (Althakafy et al, 2018) and Munz et al, achieved LOQs of 0.1 to 9 ng g −1 wet weight (Munz et al, 2018). Linearity was acceptable (R 2 > 0.98) and the chromatographic separation showed good reproducibility with an average standard deviation in retention time of ±0.015 min ( n = 5).…”
Section: Resultsmentioning
confidence: 99%
“…With the high usage of pharmaceutical and personal care products (PPCPs) in the last two decades, various PPCPs have been frequently detected in environmental matrices around the world (Althakafy et al, 2018;Spongberg et al, 2011;Zhang et al, 2015). Most PPCPs with potential hazards are present at low levels in the environment, accompanied by high polarity, and various physicochemical properties, which lead to difficulties in detection.…”
Section: Introductionmentioning
confidence: 99%
“…Among the great diversity of pollutants reaching our water supplies, pharmaceutically active compounds are one of the largest inputs . As pharmaceuticals consumption is continuously increasing , it raises concerns about their impact on the environment and undesired physiological effects they can cause to aquatic organisms . Their presence was investigated worldwide in different aquatic matrices (e.g., water, sediments, and biota) , and a large number of compounds were detected, especially in wastewaters at concentrations ranging from nanogram to microgram per liter .…”
Section: Introductionmentioning
confidence: 99%